Effects of delay in botulinum toxin treatment on patients with hyperkinetic facial disorders (Annals of Medical Research, 2023)
Aim: Hyperkinetic facial disorders include Benign Essential Blepharospasm (BEB) and Hemifacial Spasm (HFS), which involve involuntary facial muscle contractions. Botulinum toxin (BTX) is essential for relieving symptoms. The Coronavirus-19 (COVID-19) pandemic-related restrictions have led to delays in receiving BTX treatment. This study aims to assess the impact of BTX treatment delays in patients with hyperkinetic facial disorders.Materials and Methods: This study retrospectively examined the data of 84 patients (68 HFS and 16 BEB) whose BTX appointments were delayed due to COVID-19 restrictions. Patient status was evaluated using Jankovic disability rating scale (JRS) scores, and administered BTX doses were documented and compared before and after lockdown.Results: After the BTX treatment delay, the median JRS scores significantly increased from 2 before the lockdown to 3 after the lockdown (p
Keywords: Benign essential blepharospasm; Botulinum toxin; COVID-19; Hemifacial spasm